Pengaruh Kompetensi Guru Pendidikan Agama Kristen Terhadap Minat Belajar Siswa - Simanjuntak, Rusdi; Edison, Edison; Nduru, Yohanes (JURNAL IMPARTA, 2026)
This paper examines how the competence of Christian teachers in increasing students' motivation to learn. This paper uses a qualitative method with a literature study and observation approach as a primary source in obtaining data. The results of the review on this topic explain that the competencies that a teacher should have to increase the interest in learning of students, starting from having knowledge in pedagogics, personality competencies and spiritual competence. In addition, the supporting elements possessed by teachers in their competence, they must be able to solve problems in learning, have a good attitude. Teachers are encouraged to increase student motivation, because teachers are a call from God. The results of the study show that the competence of PAK teachers, which includes pedagogic, personality, social, and professional (spiritual) competencies, has a very strong influence conceptually in fostering students' interest in learning. Competent PAK teachers are able to create a dial, creative, and meaningful classroom atmosphere, so that students feel interested and motivated to learn. The conclusion of this study emphasizes that mastery of teacher competence is an absolute prerequisite for arousing students' interest in learning in a sustainable manner. The implications of this study suggest the importance of self-reflection and improving the quality of religious and pedagogical literature for PAK educators.